The significant role of traditional market in an urban context : study area : Pekan Rabu, Alor Setar and Kedai Payang, Kuala Terengganu [electronic resource] - Suziyana Alias, 1976- (2010)
Thesis (Sarjana Sains (Rekabentuk Bandar)) - Universiti Teknologi Malaysia, 2010